2022
DOI: 10.3389/fpls.2022.952074
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Functional and Phylogenetic Assembly of Plant Communities in Gobi Deserts of Northern Qinghai–Tibet Plateau

Abstract: The mechanism governing plant community assembly across large-scale Gobi deserts remains unclear. Here, we inferred the roles of different assembly processes in structuring plant communities in the Gobi deserts of the Qinghai–Tibet Plateau by using a phylogenetic tree, and leaf and root traits. The functional and phylogenetic structures of 183 plant communities were assessed, and their distributions were linked with environmental gradients. Our results demonstrated that functional convergence was prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Precipitation is scarce, with an annual average of 85 mm. The vegetation in the study area is mainly composed of drought‐tolerant and ultradrought‐tolerant shrubs, semishrubs, and small trees, as well as drought‐tolerant herbs (Wang, Wang, et al., 2022b ). Dominant species in the shrub layer include Sympegma regelii , Salsola abrotanoides , Ceratoides compacta , Ceratoides latens , Reaumuria soongorica , Haloxylon ammodendron , and Ajania fruticulosa .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Precipitation is scarce, with an annual average of 85 mm. The vegetation in the study area is mainly composed of drought‐tolerant and ultradrought‐tolerant shrubs, semishrubs, and small trees, as well as drought‐tolerant herbs (Wang, Wang, et al., 2022b ). Dominant species in the shrub layer include Sympegma regelii , Salsola abrotanoides , Ceratoides compacta , Ceratoides latens , Reaumuria soongorica , Haloxylon ammodendron , and Ajania fruticulosa .…”
Section: Methodsmentioning
confidence: 99%
“…The harsh and unique environmental conditions of the QTP desert have led to the relatively recent evolution of lineages with adaptations to survive in this cold and arid environment and subsequent adaptive radiation of species in these lineages into different parts of the region's environmental space. Previous studies have demonstrated phylogenetic and functional convergence among species in the QTP (Wang, Wang, et al, 2022b;Yan et al, 2013). Therefore, we hypothesize that taxonomic beta diversity should be substantially higher than phylogenetic and functional beta diversity and contain a dominant turnover component (H1).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The QTP is rich in plant and animal resources. To survive in this region, organisms have formed a unique adaptation mechanism in stressful environments, such as low temperatures and droughts, through natural selection for a long time, which provides good materials for the study of biological adaptability on the plateau [20]. Orinus belongs to the grass family (Poaceae) and is a genus found in alpine regions that is known for its significant economic value [21].…”
Section: Introductionmentioning
confidence: 99%